Analisis Praktek Kerjasama Pembuatan Batu Bata Perspektif Fiqih Mu’amalah di Desa Tanjungsari Kecamatan Jenangan Kabupaten Ponorogo - Nafi’ah, Nafi’ah (Fakultas Syariah INSURI Ponorogo, 2019)
People do various ways to survive, they make every effort whether they are farmers, traders, employees or other professions. Likewise, some people in the village of Tanjung Sari, Jenangan, Ponorogo, chose to become bricks managers and entrepreneurs at the brick making center in the local village. The pattern of brick- making cooperation in Tanjung Sari village, Jenangan Ponorogo sub-district has fulfilled the terms and conditions of the agreement but in terms of profit sharing there is uncertainty because the capital owner has determined the price at the beginning, deducted the amount of the manager's loan but in this case found no elements that lead to fraud and compulsion, this is in accordance with Islamic ethical ethics. Whereas the cooperation agreement between the entrepreneur (owner of capital) and the manager of the brick is classified as mud syirkah mudha>rabah but in practice there is an element of non-compliance with syirkah muda>rabah condition in terms of determining the benchmark price at the beginning when the manager borrows money to the capital owner whereas capital owners can sell middlemen with a nominal that is much higher than the price of the manager. The contract lends a certain amount of money to the brick manager, which is classified as a qardlu contract which is lively (there is an excess of benefits. Beragam cara dilakukan orang untuk bisa berhahan hidup, mereka melakukan segala upaya baik menjadi petani, pedagang, pegawai maupun profesi-profesi lainnya. Demikian juga sebagian masyarakat di desa Tanjung Sari kecamatan Jenangan kabupaten Ponorogo yang memilih menjadi pengelola dan pengusaha batu bata di sentra pembuatan batu bata di desa setempat. Pola kerjasama pembuatan batu bata di desa Tanjung Sari Kecamatan Jenangan Ponorogo telah memenuhi syarat dan rukun akad tetapi dalam hal pembagian keuntungan terdapat ketidakjelasan karena pemilik modal sudah menentukan harga di awal, dipotong besarnya pinjaman pengelola tetapi dalam hal ini tidak ditemukan unsur-unsur yang mengarah pada penipuan maupun keterpaksaan, ini sesuai dengan etika Islami keridha>an. Sedangkan Akad kerjasama antara pengusaha (pemilik modal) dan pengelola batu batu bata digolongkan sebagai syirkah muda>rabah tetapi pada prakteknya ada unsur ketidak sesuaian syarat syirkah muda>rabah dalam hal penentuan patokan harga di awal ketika pengelola meminjam uang kepada pemilik modal sedangkan pemilik modal bisa menjual batu bata ketengkulak dengan nominal yang jauh lebih tinggi dibanding dengan harga dari pengelola. Akad meminjamkan sejumlah uang kepada pengelola batu bata tergolong dalam akad qardlu yang jarra naf’an (adanya kelebihan manfaat).",